Deoxyribonucleic Acid Base Composition and Hybridization Studies on the Human Pathogen Sporothrix schenckii and Ceratocystis Species - Mendonça-Hagler, Leda C. (1974)
Deoxyribonucleic acid (DNA) base composition, as measured by guanine plus cytosine (G + C) content, was determined in 17 strains of Sporothrix schenckii and Ceratocystis species. The average G + C content for S. schenckii was 54.7 ± 0.2 mol%. No strain of Ceratocystis, with the exception of C. minor, gave values for G + C content similar to those obtained for S. schenckii. All DNA samples from strains of S. schenckii cross-hybridized with high percentages of relative binding. DNA samples from C. stenoceras and C. pilifera showed low degrees of homology with S. schenckii DNA. The DNA from C. minor hybridized with 75% binding with that from a strain of S. schenckii, as compared with the homologous reaction.